The impact of metropolitan areas on internal migrations in Poland. The case of southern regions - Michal Bernard Pietrzak; Justyna Wilk (Institute of Economic Research (IER), 2013)
Metropolitan areas significantly affect regional development. They attract an inflow of investments, innovations and know-how as well as create domestic population migration flows. Relocation of human resources regulates both a size and structure of population, supports regional labour markets, the demand for goods stimulation, etc. The objective of this paper is to discuss the impact of metropolitan areas on domestic migration flows concentrating on southern area of Poland. The empirical study covers subregions and counties and refers to the period of 2008-2010 corresponding to global financial and economic crisis. Ratio analysis as well as taxonomical analysis was applied in the research. Research results show that southern Polish subregions demonstrate low intensity of intraregional population movements while interregional flows are quite significant, in particular within the territory of southern Poland. The majority of migration flows occur in relation to the city of Wroclaw and the city of Cracow, due to their metropolitan capacity.
Keywords: J11; O11; R11; R23; 330; internal migration; metropolitan areas; ratio analysis; synthetic measure